(untitled) (Indian Journal of Animal Production and Management, 2016)
The present study was conducted on Barbari kids to assess the effect of probiotics supplementation on biochemical parameters. A total 18 Barbari kids were selected and randomly distributed in three groups. The 1st group (T1, n=6) was kept control fed (basal ration) without supplementation, the group 2nd (T2,n=6) was supplemented with Lactobacillus acidophillus @ 2g/animal/day and group 3rd (T3, n=6) was supplemented with Saccharomyces cerevisiae @ 2g/animal/day. Higher serum blood glucose, total protein and albumin level was observed at monthly interval in probiotics supplemented group as compared to unsupplemented group. Lower serum cholesterol level was observed in supplemented group T2 and T3 as compared to control group T1.